2023
DOI: 10.15561/26649837.2023.0209
|View full text |Cite
|
Sign up to set email alerts
|

Blood types and fitness capability of physical education students: a non-parametric analysis

Abstract: Background and the Study Aim. The study describes the association of blood types and physical fitness capability of physical education students. Material and Methods. A non-parametric analysis was used in the study employing chi-square with the Cramer’s V analysis to provide the likelihood relationship between variables. Using the simple random sampling, there were 263 participants composed of 198 (75.3%) females and 65 (24.7%) males. The samples were all students from physical education subject with the age r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recently, there are studies that shown possible relationship between movement capability and physical activity. It is believed that individuals with higher motivation and support from the school and parents are more likely to engage in regular physical activity (Garcia, Bojos, & Sy, 2021), blood types (Garcia & Canillas, 2023), and biological factor and psychological factor (Garcia,2022). Thus, improving movement capability may effectively increase physical activity levels and promote overall health (Warburton, Nicol, & Bredin, 2006).…”
Section:  Introductionmentioning
confidence: 99%
“…Recently, there are studies that shown possible relationship between movement capability and physical activity. It is believed that individuals with higher motivation and support from the school and parents are more likely to engage in regular physical activity (Garcia, Bojos, & Sy, 2021), blood types (Garcia & Canillas, 2023), and biological factor and psychological factor (Garcia,2022). Thus, improving movement capability may effectively increase physical activity levels and promote overall health (Warburton, Nicol, & Bredin, 2006).…”
Section:  Introductionmentioning
confidence: 99%